Effects of Lifestyle Measures, Antiobesity Agents, and Bariatric Surgery on Serological Markers of Inflammation in Obese Patients - Konstantinos Tziomalos; Hariklia V. Dimitroula; Niki Katsiki; Christos Savopoulos; Apostolos I. Hatzitolios (Hindawi Limited, 2010)
Overweight and obesity are highly prevalent in developed countries and are also becoming more frequent in the developing world. Overweight and obese patients have elevated levels of several inflammatory markers and this inflammatory state might contribute to their increased vascular risk. We summarize the effects of lifestyle changes, antiobesity agents, and bariatric surgery on serological inflammatory markers in overweight and obese patients. Most studies showed a decrease in inflammation with all 3 interventions. However, it remains to be established whether the decrease in inflammatory markers induced by lifestyle changes or (where indicated) with antiobesity agents or bariatric surgery will translate into reduced vascular morbidity and mortality in overweight and obese patients.